Facial Feature Reconstruction using Structure from Motion - Rautenbach, Pieter Albertus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.